HEREDITARY ANGIOEDEMA: CLINICAL CHARACTERISTICS AND CURRENT THERAPEUTIC APPROACHES - Alicja Nowik; Julia Mazurek; Joanna Kośka; Julia Załęcka; Katarzyna Moliszewska; Paweł Kukiełka; Michał Błaszkiewicz; Kacper Dywan; Martyna Musiorska (International Journal of Innovative Technologies in Social Science, 2025)
Hereditary angioedema (HAE) is a condition characterized by recurrent edema caused by the dysfunction of bradykinin production. Advances in understanding the pathophysiology of this disease have changed the diagnostic approach, acute management and prophylaxis. Optimal treatment now combines early diagnosis, targeted therapy and patient education. This narrative review provides an overview of current evidence regarding the clinical presentation, treatment options and promising new therapies for HAE. A systematic search of the PubMed and Google Scholar databases was conducted using terms such as hereditary angioedema, therapeutics, C1 inhibitor deficiency, bradykinin and disease management. Additional relevant studies were identified by manually reviewing reference lists and citations. The basis for effective treatment is an accurate diagnosis based on clinical symptoms, family history, and laboratory test results. On-demand treatment, such as C1 esterase inhibitor (C1-INH), icatibant, and ecallantide provides rapid symptomatic control. Long-term prophylaxis with agents such as lanadelumab, berotralstat or plasma-derived C1 esterase inhibitor (pdC1-INH) significantly reduces the frequency of attacks and improves patients’ quality of life. New data confirm that modern biologic therapies can maintain disease control with a favorable safety profile. Current HAE treatment strategies emphasize personalized prophylaxis, adequate intervention in acute attacks and continuous patient education. Combining modern therapies with individual patient preferences improves daily functioning, mental well-being and overall prognosis.